Deformacijska analiza po postopku Caspary - Hamza, Veton (Geodetski vestnik, 2020)
In this paper, the theoretical background of the Caspary method of geodetic deformation analysis is described and implemented in a simulated geodetic network in which two epochs of measurements are used. The Caspary approach foresees congruence testing of the geodetic network, the determination of the stable points between two analysed epochs, the transformation of the geodetic network using S-transformation, the calculation of displacements, and, in the last step, the graphical presentation of displacement vectors. Results obtained from the presented example are similar to those presented in the Hannover, Karlsruhe, Delft, Fredericton, München, and robust methods.
Keywords: Caspary approach; deformacijska analiza; deformation analysis; geodesy; geodetic network; geodetska mreža; geodezija; meritve; numerical example; observations; postopek Caspary; računski primeri